Polypropylene Polymerization and Characterization of Mechanical and Thermal Properties - Wang, Weiyu; Zeng, Yiming (IntechOpen, 2020)
Polypropylene (PP) is one of the most important thermoplastics widely applied in the fields of automobile, packaging, clothing, and plastic molding. Since J. Paul Hogan and Robert L. Banks accidentally synthesized crystalline PP in 1951, tremendous breakthroughs have been achieved and have successfully transferred PP from a discovery in the laboratory to an indispensable commodity. Along with the commercial success, progress in the "academic community" of PP has expanded our toolbox to tailor tactility and microstructure, improve thermal and mechanical properties, understand and control crystallization behavior, develop efficient functionalization strategies, and explore novel applications. This book provides an overview of progress in PP from the perspectives of synthesis, structure-property relationship, processing, PP composites, and applications.